Hubungan Asupan Energi, Karbohidrat dan Lemak dengan Status Obesitas pada Lansia di Posyandu Lansia Wedra Utama Purwosari - Rahayu, Novia Tri; , Setyaningrum Rahmawaty, A., M. Kes, Ph.D; , Siti Zulaekah, A., M.Si (2017)
The nutrition given for the elderly is important to avoid the malnutrition problem. Inappropriate dietary intake can lead to obesity. Results based on Riskesdas, 2013 show that obesity in elderly has increased at 18.10% since 2007. Based on the preliminary surveys conducted in Posyandu Lansia Wedra Utama, 46.42% of the elderly are obese. To determine the relationship of energy, carbohydrates and fats intake with obesity status of elderly in Posyandu Lansia Wedra Utama Purwosari. The research was an observational study with cross sectional approach. Thirty-three elderly were participated in this study recruited using simple random sampling technique. The data of energy, carbohydrate and fat intake were obtained using semi-quantitative Food Frequency Questionnaire, weight and height was measured using bathroom scale and microtoice respectively. Pearson Product Moment test of SPSS for Windows version 21.0 was used to analyze the relationship between energy, carbohydrate and fat intake and obesity status in the elderly. Twelve (36.4%) elderly have sufficient energy intake, 11 (33.3%) elderly have less carbohydrate intake, 15 (45.5%) elderly have poor fat intake and 18 (54.5%) elderly obesity stage I (IMT= 25.0-29.5kg/m2). There are no relationship between energy, carbohydrates and fats intake and obesity status of the elderly, with p value 0.622, 0.800 and 0.136 respectively